HETEROSIS AND COMBINING ABILITY ANALYSIS IN BITTERGOURD (MOMORDICA CHARANTIA L.) - A. K. SINGH,; R. S. PAN,; P. BHAVANA, (The Bioscan, 2013)
Twenty one crosses along with their parents were studied for combining ability, heterosis and gene action for eight yield and yield components in bittergourd. Except days to 50% flowering significant differences were observed for all the characters under study. All the traits were found under the control of non additive gene action except for fruit length and fruit breadth which showed significant differences due to both gca and sca with preponderance to additive gene action. HABG-30 was found to be good general combiner for most of the characters (yield/plant, yield t/ha, fruit weight, fruit length, fruit breadth and vine length). HABG-24XHABG-30 exhibited significant sca effect for all characters except days to 50% flowering and HABG-23XHABG-34 showed significant sca effect for number of fruits/plant, yield/plant, yield t/ha and vine length. These crosses were also found to show significant heterosis in the desired direction for most of the yield characters. Hence they can be exploited as desirable hybrids.